Deteksi Wajah Menggunakan Hidden Markov Model (HMM) Berbasis Matlab - Nur Widya Pratiwi; Fauziah Fauziah; Septi Andryana; Aris Gunaryati (Universitas Indraprasta PGRI Jakarta, 2018)
Face is a part of the body that can be detected. It makes face the basis of a detection system. The system can detect the object of face from an input image. The research develops the face detection system using Hidden Markov Model (HMM) method. The system is a computer technology allowing identification or verification of a person's face through an image. The workings of face detection system is by matching a face image with face image stored in file. Unlike the previous system that can only detect black-and-white pictures or images, the system created in this research is an update that can detect black-and-white and color pictures or images. This face detection system uses MATLAB software for its program and Guide MATLAB for its design. From the experiments and tests performed, the application can detect face image with success rate up to 95.9%. This proves the tool is quite good in face recognition or detection.